A comparison of methods for excluding light from stems to evaluate stem photosynthesis - Valverdi, Nadia Antonella; Acosta, Camilla; Dauber, Gabriella R.; Goldsmith, Gregory R.; Ávila‐Lovera, Eleinis (Wiley, 2023)
Premise: A comparison of methods using different materials to exclude light from stems to prevent stem CO2 exchange (i.e., photosynthesis), without affecting stem conductance to water vapor, surface temperature, and relative humidity, was conducted on stems of avocado trees in California. Methods and Results: The experiment featured three materials: aluminum foil, paper-based wrap, and mineral-based paint. We examined stem CO2 exchange with and without the light exclusion treatments. We also examined stem surface temperature, relative humidity, and photosynthetic active radiation (PAR) under the cover materials. All materials reduced PAR and stem CO2 exchange. However, aluminum foil reduced stem surface temperature and increased relative humidity. Conclusions: Methods used to study stem CO2 exchange through light exclusion have historically relied on methods that may induce experimental artifacts. Among the methods tested here, mineral-based paint effectively reduced PAR without affecting stem surface temperature and relative humidity around the stem.